The association between interparental conflict and problematic internet use among Chinese adolescents: Testing a moderated mediation model. (September 2021) - Wang, Lin-Xin; Dou, Kai; Li, Jian-Bin; Zhang, Ming-Chen; Guan, Ji-Yao
Abstract: Interparental conflict is a risk factor for adolescent problematic internet use (PIU), but little research has investigated the processing mechanisms underlying this association. Based on the future time perspective theory, this study tested the idea that interparental conflict would be associated with adolescent PIU via restraining the protective effect of future positive time perspective (FPTP) and boosting the deleterious effect of future negative time perspective (FNTP). Moreover, drawing upon the ecological system theory, this study also investigated the interplay between interparental conflict and teacher-student relationship in relation to future time perspective and further to PIU. Using three-wave longitudinal data, with each time point spanning three months apart, this study examined the aforesaid questions in 523 Chinese adolescents (276 boys, M age  = 14.64 years). Results of moderated mediation model found that after controlling for T1 PIU, T1 interparental conflict was associated with T3 PIU through T2 FNTP. Moreover, a stronger teacher-student relationship played a protective role for adolescents less exposed to interparental conflict. These findings provide nuanced explanation about h ow and for whom interparental conflict is associated with PIU in adolescents. The results also shed light on effective prevention and intervention strategies to mitigate adolescent PIU in the Chinese context. Highlights: Interparental conflict was positively correlated with adolescent problematic Internet use. Future negative time perspective mediated the link between Interparental conflict and problematic Internet use. Teacher-student relationship would moderate the mediation effect of future negative time perspective.